Impact, impression, and innovations of objective structured practical examination in biochemistry curriculum of medical undergraduates - Chakraborty, Sanghamitra; Gupta, Soma (Asian Journal of Medical Sciences, 2022)
Background: In the recent years, there is a huge paradigm shift of medical education in India from curriculum-based learning to learner-centered and time independent competency-based medical education. This paradigm shift was to rear and trains medical graduates to function as physician of first contact being globally acceptable. Due to this, the felt need of the hour was to find an assessment tool that is valid, reliable, devoid of subjective bias, and has the capabilities to assess the cognitive, psychomotor, and effective domain. Aims and Objectives: In this context, this study was done to assess the impression and impact of objective structured practical examination (OSPE) in comparison to conventional practical examination (CPE). Due to the ongoing pandemic of COVID-19, there was some scope of organizing OSPE in virtual mode. Materials and Methods: The study involved of 250 Phase I medical undergraduates of Nil Ratan Sircar Medical College. The response stations included charts, clinical problems, graphs, pictures, and critical analysis of reports. Results: The mean scores in OSPE were higher than CPE. In our study, 51.3% strongly voiced that conducting OSPE was more scientific with uniformity in evaluation. Conclusion: OSPE was preferred by the students as an assessment tool. Moreover, OSPE had a scope to be organized in Virtual mode.